Locating new chiropractor practices in England and Wales - Maina, Njiraini John (International Journal of Scientific Research and Management (IJSRM), 2018)
Chiropractor practice is the non use of drugs in healing. In the United Kingdom, these services are not paid for by the Government through the National Health Service but patients must pay for the said services. Chiropractor clinics are increasing becoming popular but are unevenly distributed with their location being subject to both sickness (demand) and ability to pay for the services. In need to establish new clinics in light of increasing demand, this study uses Geographical Information System and statistical analyses to locate optimal location of new clinics. Key factors considered are area’s deprivation, illnesses and poverty as recorded in UK’s 2001 census data. Areas’ deprivation is found to be of less importance in selecting the optimal location areas due to its multiple characters whereas illness, distance from existing clinics and ability to pay are the main determinants. Twenty proposed optimal clinic areas in England and Wales are eventually modelled. These would be used in new establishment with an aim of serving the increasing chiropractor practices demand in the two countries